Second Primary Tumors in Patients with Head and Neck Cancer - Martins Priante, Antonio Vitor; Castilho, Emanuel Celice [UNESP]; Kowalski, Luiz Paulo (Springer, 2011)
This is a review on second primary tumors in patients with head and neck cancer. These patients have a high risk of developing other cancers simultaneously or subsequently. The incidence of multiple primary tumors in this population can be as high as 27%. Recurrences are the most common cause of treatment failure within the first 2 years of follow-up. After the third year the diagnosis of a second primary tumor becomes the most important cause of morbimortality in head and neck cancer patients, especially in those treated for cancers early diagnosed. Most second primary tumors occur in the upper aerodigestive tract (40%-59%), lung (31%-37.5%), and esophagus (9%-44%). Patients who develop second primary tumor have a significant reduction of survival expectancy.
Keywords: Multiple primary tumors; Second primary tumors; Head neck; Triple endoscopy; Surveillance